Influência do armazenamento à campo na propagação vegetativa de espécies reófitas - Weise, Vinicius de Oliveira (2019)
The implementation of techniques in Soil Bioengineering depends on the characteristics of species of plants to be used in interventions, therefore, the knowledge regarding the vegetation integrates the basis of necessary information for the implementation of a specific technique. One of the important aspects related to plant behavior is the multiplication capacity through vegetative propagation, mainly when the plan takes roots by cuttings. Plant cuttings is one of the most used techniques in combining inert material, calling attention to great dimension projects of Soil Bioengineering, its demand might influence the working schedule, making it necessary to storage the material until all the collecting is ready, in order to be able to follow to the plantation phase. This study aimed at investigating the storage methods of cuttings and efficient techniques while using the native Rheophytes species, which have their potential for vegetative propagation already known, together with methods which do not use artificial refrigeration, however, they are capable of decreasing the degrading effects caused by the solar effect, wind and high temperatures. The species used were: Gymnanthes schottiana (Müll. Arg.) Müll. Arg., Phyllanthus sellowianus Müll. Arg., Salix humboldtiana Willd. and Sesbania virgata (Cav.) Pers. in a completely randomized design, two-factor style (3x3), where the cuttings were exposed to 3 types of storage (partially submerged in water, wrapped in black plastic tarp and stored in a shady place, all under a cover of netting with 50% of light block, for 3 periods of storage (30, 45 and 60 days) previously to the plantation, besides a control treatment (Witness) which consisted in the plantation of the cuttings on the harvesting day. After the plantation in individual plastic vases with sifted sand, the cuttings were conducted to greenhouses for 45 days with irrigation, environmental relative humidity, lighting and automated controlled temperature. After the period of plantation, the surviving data were collected (%), sprout length sum (cm), root dry matter (g), sprout dry matter (g) and number of sprouts. The main factor to be analyzed was the surviving rate of the species in each treatment, where 70% was defined as the minimum considered satisfactory, which was reached in 6 treatments for P. sellowianus, 5 for G. schottiana, 4 for S. humboldtiana and in one for S. virgata, confirming the feasibility of vegetative propagation of cuttings after storage in subtropical climate without using artificial refrigeration.